PENERAPAN ASAS FIDUCIARY DUTY TERHADAP DIREKSI DALAM PELANGGARAN KLAUSULA NEGATIVE COVENANTS PERJANJIAN KREDIT: Application of The Principle of Fiduciary Duty to Directors in Violation of The Negative Covenants Clause of a Credit Agreement - Putri, Denisya Adriana Maharani; Sanusi, Heru Pringgodani (AMICUS CURIAE, 2025)
The Board of Directors as the management of the company is responsible for overseeing and managing the business in accordance with the company's articles of association and the regulations contained in Law 40 of 2007 concerning Limited Liability Companies. One of the principles that guides the responsibility of the Board of Directors in carrying out its role as the management of the company is Fiduciary Duty. The problem discussed relates to the violation of the negative covenants clause in the credit agreement of PT Hair Star Indonesia. PT Bank OCBC NISP Tbk filed a lawsuit with a tort claim against the directors of PT Hair Star Indonesia because the Directors of PT Hair Star Indonesia were considered negligent in carrying out their responsibilities so that the veil of the company was torn and Piercing the Corporate Veil became applicable. As a result, PT Bank OCBC NISP Tbk suffered losses as a result of the violation of the principle of Fiduciary Duty committed by the Directors of PT Hair Star Indonesia in managing the company. The research methodology used is descriptive normative with secondary data sources and deductive approach.